Rise and fall of the Franchini Family: A sad case of fraud - Elisa Dalla Rosa (The Journal of European Economic History (JEEH), 2025)
The paper focuses on the history of an entrepreneurial family, member of the local élite of Verona in between the old typographical regime and the modern publishing industry. It also describes the rise and fall of a family company with large interests in the field of printing, cardboard manufacture, the agricultural sector and with a key role in the economic development of the Verona's area in the 19th century. The sale of the printing activity to Arnoldo Mondadori and the failure of the cardboard manufacturer represent the sad epilogue of the Franchini Family as well as of their economic activities and membership of the Veronese élite in the early decades of the 20th century.
Keywords: 330; Familienunternehmen; Elite; Unternehmensgeschichte; Verlagswesen; Papierindustrie; Verona; Italien